(untitled) (Bangladesh Journal of Plant Taxonomy, 2020)
A new species, Utricularia rosettifolia Alfasane & Hassan (Lentibulariaceae), is described with illustration. Detailed taxonomic description including information on type specimens, flowering and fruiting time, ecology, and distribution in Bangladesh are provided. The diagnostic characters of this species and comparison with its closest one are also provided. Bangladesh J. Plant Taxon. 27(2): 205-211, 2020 (December)